Inventario biológico rápido para la identificaión de las especies de la familia fabaceae en la parte sur, como aporte a la propuesta de área de conservación regional bosques de Shunte y Mishollo, provincia de Tocache, región San Martín - Pasapera Vásquez, Adan Ricardo (2014)
In this thesis "biological inventory fast the identification of the species of the Fabaceae family in the southern part, as a contribution to the proposal for a Regional Conservation Area Shunte Forests and Mishollo, in Tocache province, San Martin Region" developed in the southern part of the proposals Regional Conservation Area Shunte Forests and Mishollo, located in Tocache province, San Martin Region, is part of a draft inventory of flora and fauna to publicize the floristic richness of the area; in itself this thesis has as objective to give a contribution with reliable information; in this sense the scientific group described in Annex 5 using an IBR made identify 26 species belonging to the family Faba cea e Aba rema auriculata, Aba rema jupunba, Aba rema sp, Andira multistipula, Clitoria arbórea, Diplotropis sp, Dussia tessmannii, Enterolobium cyclocarpum, lnga sp, lnga punctata, lnga vera cf, Machaerium sp, Ormosia sp, Pueraria sp, Stryphnodendron sp, Tachigali pilosula ined y Tachigali setifera, Abarema sp, Cassia sp, Crotalaria sp, Desmodium sp, Diplotropis sp, lnga sp, Machaerium sp, Ormosia sp, Pueraria sp, Spirocarpus sp y Stryphnodendron sp, Cassia sp, Crotalaria sp, Desmodium sp, Erythrina edulis, lnga sp, lnga marginata, Mucuna rostrata y Spirocarpus sp, Desmodium sp, Erythrina edu/is, Erythrina ulei, lnga sp, lnga sertulifera cf y Mucuna rostrata; these species were recorded in an altitudinal range between 850 to 2100 msnm, being the altitudinal range between 850 to 1500 msnm which record highest number of species of the family Fabaceae; likewise within the 26 recorded species identified 04 new species Abarema auriculata, Aba rema jupunba, Enterolobium cyclocarpum e lnga punctata with new record for San Martin; the species lnga sp is the one that was found in the majority of the sampling plots. In regard to the taxonomic classification were classified a total of 18 genera and 26 species being the genus lnga which recorded more species identified in a total of 5, Gender Abarema recorded 3 species, the genera Erythrina and Tachigali with 2 species each and the kind Andira, Cassia, Clitoria, Crota/aria,